2011
DOI: 10.1128/mcb.00811-10
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Alpha and Inflammation Disrupt the Polarity Complex in Intestinal Epithelial Cells by a Posttranslational Mechanism

Abstract: Inflammatory processes disrupt the barrier function in epithelia. Increased permeability often leads to chronic of inflammation. Important among other cytokines, tumor necrosis factor alpha (TNF-␣) initiates an NF-B-mediated response that leads to upregulation of myosin light chain kinase (MLCK), a hallmark of the pathogenesis of inflammatory bowel disease. Here, we found that two components of the evolutionarily conserved organizer of tight junctions and polarity, the polarity complex (atypical protein kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 50 publications
(67 reference statements)
7
52
1
Order By: Relevance
“…However, recent studies suggest that damage of colonic stem cells could be a major cause [13][14][15] . In addition, disruption of epithelial cell contacts could be important in the pathological process as the loss of tight junctions of colonic epithelial cells was observed in DSS-induced colitis [40][41][42] . We observed that Myh9 was upregulated in DSS-induced colonic epithelial injuries and in Lgr5 þ stem cells on dissociation.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies suggest that damage of colonic stem cells could be a major cause [13][14][15] . In addition, disruption of epithelial cell contacts could be important in the pathological process as the loss of tight junctions of colonic epithelial cells was observed in DSS-induced colitis [40][41][42] . We observed that Myh9 was upregulated in DSS-induced colonic epithelial injuries and in Lgr5 þ stem cells on dissociation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, proinflammatory tumor necrosis factor α (TNFα) signaling suppresses atypical protein kinase C (PKCζ) level via NFκB dependent abrogation of Hsp70/Hsc70 chaperoning activity and interrupts PKCζ-Par3-Par6 polarity complex activity that is critical for maintenance of epithelial polarity [99, 100]. PKCζ activity can be rescued by NFκB inhibition [99]. However, NFκB activity is also critical for maintenance of intestinal epithelial barrier [101].…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the implication for the recently discovered crosstalk between aPKC signaling and NF-kB activity (pathway summarized in supplementary material Fig. S1) (Forteza et al, 2013;Mashukova et al, 2011), our results highlight functional differences between cytosolic Hsc/Hsp70 (which represents the bulk of these chaperones) and a small but functionally relevant pool of keratin-bound Hsc/Hsp70. BAG-1 is expressed within a broad range of concentrations in different cell types (Mäki et al, 2007;Nollen et al, 2000).…”
Section: Bag-1 Is Necessary For the Effect Of Tnfa On Posttranslationmentioning
confidence: 89%
“…The levels of phosphorylated protein generally parallel those of total protein. However, whereas the former are a direct result of Hsp70 chaperoning followed by PDK1-mediated phosphorylation and then autophosphorylation, the total protein reports on the ubiquitylation and proteasomal degradation (Mashukova et al, 2009;Mashukova et al, 2011). For simplicity, the levels of active conformation, phosphorylated turn domain aPKC are referred to as aPKC levels.…”
Section: Introductionmentioning
confidence: 99%